2016
DOI: 10.15835/buasvmcn-asb:12320
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ascorbic acid on in vitro maturation of canine oocytes

Abstract: It is known that L-ascorbic acid (vitamin C) can modulate many biochemical processes intracellularly or extracellularly as antioxidant. The aim of the present study was to examine the effects of media supplementation with ascorbic acid on canine oocyte meiotic maturation, viability and the cumulus cell expansion. Various concentrations of ascorbic acid supplemented in in vitro maturation (IVM) media were tested. Canine oocyte was exposed to different levels of ascorbic acid (0, 50, 150, 250, 500, 750µM). Cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Nuclear maturation status achieved with addition of ascorbic acid is comparable to findings of Pernes et al, (2016) who found that ascorbic acid increased the meiotic resumption of canine oocytes and higher proportions of oocytes reached MI and MII stage. Significant improvement in maturation rate of MII oocytes with ascorbic acid supplemented media were reported by Dorra et al, (2012) and Nadri et al, (2009) in rabbit and mice oocytes, respectively.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Nuclear maturation status achieved with addition of ascorbic acid is comparable to findings of Pernes et al, (2016) who found that ascorbic acid increased the meiotic resumption of canine oocytes and higher proportions of oocytes reached MI and MII stage. Significant improvement in maturation rate of MII oocytes with ascorbic acid supplemented media were reported by Dorra et al, (2012) and Nadri et al, (2009) in rabbit and mice oocytes, respectively.…”
Section: Resultssupporting
confidence: 79%
“…It inhibited the apoptosis in bovine granulosa cells and murine cumulus oocyte complexes (Tilly and Tilly, 1995;Eppig et al, 2000;Murray et al, 2001), reduced intracellular levels of reactive oxygen species (Castillo-Martín et al, 2014b) and heat shock protein 70 (HSPA1A) (Castillo-Martín et al, 2014a). As antioxidant supplement, ascorbic acid has many beneficial effects including improvement of nuclear maturation and developmental competence of oocytes matured in vitro (Pernes et al, 2016). The role of ascorbic acid as antioxidant on in vitro maturation of oocytes is documented by various authors in literature; however the studies on the effect of ascorbic acid on in vitro maturation of oocytes under heat stress are very less.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro embryo production is necessary in order to obtain high quality embryos that are used in reproductive biotechnology, as well as in research [ 4 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the practice of IVF ascorbic acid has often been used in different concentrations as a supplement in in vitro culture systems for embryos but also for the maturation of domestic cat oocytes [ 9 ], buffalo and bovine oocytes [ 10 , 11 ], canine oocytes [ 12 ] or pig oocytes [ 8 ]. The better results in their studies were with 50 µg/mL ascorbic acid in bovine oocytes [ 11 ], 50 µM for buffalo oocytes [ 10 ], 250 µM for canine oocytes [ 12 ], or 250 µM for pig oocytes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation